Analisis Risiko dalam Investasi Islam - Irkhami, Nafis (MUQTASID, 2010)
Business activities and investments can not be separated from risk, because the return is a result of risk analysis. Based on its nature, it is no small investment activities, especially in the field of financial assets, which in fact exploit the conditions in a way to speculate. In many cases, these speculators caused often create economic inequality, even crisis. This article will find footing construction investment ethical analysis of Islamic pespectives, including the instruments of the screening process, as well as the concept of Islamic investment analysis of risk and return. Â  Keywords: Islamic ethical investment, investment analysis, risk